“Głuszec”, “Pieun”, “Śpiewak” – the Names of the Game Bird Perpetuated in the Novels of Józef Weyssenhoff - Płusa, Magdalena (Respectus Philologicus, 2023)
This article focuses on the names of the game bird (capercaillie) as recorded in two literary works by Józef Weyssenhoff, namely Puszcza and Soból i panna. These novels provide research material regarding the terms used to refer to the wild bird, namely głuszec, pieun, śpiewak. The names, supported by examples from the mentioned texts, were examined in terms of their documentation (formal and semantic), in various sources, such as dictionaries, regionally-derived lexical elements, collections of hunting vocabulary, nature studies and literature. The findings show that the author used not only the wildly known name (głuszec) but also confirmed the presence in the hunting terminology (pieun, śpiewak) with very scant documentation (sometimes only from Weyssenhoff).